Main Street, and Other Poems - Kilmer, Joyce, 1886-1918 (Salt Lake City, UT : Project Gutenberg, 2008)
"Main Street, and Other Poems by Joyce Kilmer" is a collection of poetry written in the early 20th century. The volume reflects the sentiments and aesthetics of wartime and the everyday experiences of life, showcasing themes such as nature, love, community, and the impacts of war. Kilmer's work often intertwines personal emotions with broader human experiences, presenting a poignant exploration of existence through a lyrical lens. The collection includes a variety of poems that express nostalgia for simpler times, appreciation for nature, and reflections on love and loss. The titular poem "Main Street" evokes a sense of familiarity and comfort through vivid imagery of a small-town street in different seasons, contrasting it with the coldness of busy city life. Other poems, like "In Memory" and "Easter Week," delve into deeper themes, touching on grief and the enduring spirit of humanity amidst adversity. Kilmer's work is characterized by its emotional depth and rhythmic beauty, making it a thoughtful read for anyone interested in the interplay of personal experience and collective memory during a tumultuous era. (This is an automatically generated summary.)
Release date is 2008-07-09
Produced by A. Light, and Linda Bowser, and David Widger
Keywords: City and town life -- Poetry; Poetry, Modern -- 20th century